Metabolit Skunder Buah Rambusa(Passiflora feotida L) Sebagai Anti-Bakteri Pada Tanaman - Rifqah Aulia; Intan Surullah Sutoro (Agriculture Faculty of Flores University, 2023)
Rambusafruit (Passiflora feotida L.) is a type of wild plant that can be consumed like passion fruit, therefore this fruit is also known as forest passion fruit. Besides being consumed, this fruit can also be used as medicine in humans, such as for the treatment of diarrhea caused by Escherechia coli bacteria. This condition opens up opportunities for the use of Rambusafruit as an anti-bacterial that causes disease in plants. Based on the above phenomenon, the purpose of this study was to determine the secondary metabolic content of the rambutan fruit extract. Laboratory test results through phytochemical tests proved that the rambutan fruit extract contains secondary compounds that have potential as anti-bacterials, including saponins, flavonoids, tannins, triterpenoids, steroids and essential oils.